Printable ink lenses, diffusers, and 2D gratings. Issue 1 (1st December 2016) - Ahmed, Rajib; Yetisen, Ali K.; Khoury, Anthony El; Butt, Haider
Abstract : Advances in holography have led to applications including data storage, displays, security labels, and colorimetric sensors. Abstract : Advances in holography have led to applications including data storage, displays, security labels, and colorimetric sensors. However, existing top-down approaches for the fabrication of holographic devices are complex, expensive, and expertise dependent, limiting their use in practical applications. Here, ink-based holographic devices have been created for a wide range of applications in diffraction optics. A single pulse of a 3.5 ns Nd:YAG laser allowed selective ablation of ink to nanofabricate planar optical devices. The practicality of this method is demonstrated by fabricating ink-based diffraction gratings, 2D holographic patterns, optical diffusers, and Fresnel zone plate (FZP) lenses by using the ink. The fabrication processes were rationally designed using predictive computational modeling and the devices were fabricated within a few minutes demonstrating amenability for large scale printable optics through industrial manufacturing. It is anticipated that ink will be a promising diffraction optical material for the rapid printing of low-cost planar nanophotonic devices.